Computational studies of buildings' thermal state - Хованський, Сергій Олександрович; Колісніченко, Едуард Васильович; Панченко, Віталій Олександрович (Technology audit and production reserves, 2015)
This article deals with applying numerical methods of thermal condition modeling of buildings and their component parts in heat-and-power engineering. Some research results in this area are also presented. The main purpose of the study is to improve energy efficiency of buildings’ thermal power on the basis of thermal conditions analysis. The object of the study is the thermodynamic parameters of the thermal state of the buildings heated by radiators of radiative-convective type. This article presents methods of modeling of aerodynamic and heat transfer processes in the buildings with the help of software package ANSYS CFX. The research results can be applied by energy auditors in the field of heat-and-power engineering to assess compliance of the comfortable conditions inside the building, to analyze its thermal state, to assess the effectiveness of various energy-saving measures.